Cowden syndrome is a risk factor for ischemic stroke - T. A. Valikova; V. M. Alifirova; E. S. Koroleva; M. N. Filimonova; N. V. Pugachenko (Бюллетень сибирской медицины, 2017)
Cowden syndrome is a rare genetic disorder caused by the abnormal development of all three germ layers. Taking into consideration the mesodermal origin of mesenchymal tissue that gives rise to the vascular system, the pathology of cerebral blood vessels can occur in conjunction with this disease and cause the development of cerebrovascular disease in such patients.